Analisis Kebutuhan Pengembangan Peta Perjalanan Haji Berbasis Animasi untuk Meningkatkan Pemahaman Materi - Farhan Maulana Arli (TSAQAFATUNA : Jurnal Ilmu Pendidikan Islam, 2026)
The teaching of Fiqh, particularly the topic of Hajj at the Madrasah Tsanawiyah level, faces significant challenges due to the dominance of lecture-based methods and the limitations of conventional learning media. This condition makes it difficult for students to visualize the sequence and movement between Hajj ritual locations chronologically, resulting in partial understanding and a higher risk of misconceptions. This study aims to analyze the needs for developing an animated Hajj journey map as an innovative learning medium to enhance students’ understanding at MTsS Lam Ujong, Aceh Besar. The research employed a Research and Development (R&D) approach using the ADDIE development model, specifically focusing on the needs analysis stage. This stage comprehensive involved analyses of school needs, instructional needs, student needs, and teacher needs. The findings indicate that teachers require learning media capable of dynamically visualizing transitions between Hajj ritual locations, while students need visual and auditory stimulation to better understand and retain the stages of Hajj rituals. Based on these insights, a conceptual framework for a learning medium is proposed, integrating animated visuals, location maps, audio narration, and interactive quizzes accessible via standard school facilities. This preliminary study serves as a crucial foundation for further research to complete the subsequent stages of the ADDIE model and empirically evaluate the developed media.